PERANCANGAN IKLAN KAMPANYE TRUNK AND FEEDER MELALUI INFOGRAFIS SEBAGAI UPAYA PENGENALAN TRANSPORTASI BARU DI KOTA SURABAYA - Cahyadi, Ari Bima Putra; Budiardjo, Hardman; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
The purpose of designing advertising campaigns Trunk and Feeder as the new public transport Surabaya is to raise awareness of the status of the transport and traffic impact on congestion in the city of Surabaya. Further research was conducted using qualitative research methods that do interviews, observation, documentation, and literature to obtain the data used to support the manufacture of the design concept of the ad campaign. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. After analyzing the data, found a design concept or keyword advertising campaign namely "Impressive". Description of "Impressive" is Memorable. The concept of "Impressive" aims to show that the Trunk and Feeder are expected to have an impression in the eyes of the public using public transport compared with the previous public transport. That is, the impressive concept presented to instill public perception, that the Trunk and Feeder is public transportation memorable. Results from the design ad campaign is to raise awareness of the state of transportation in the city of Surabaya, which if left unchecked will cause congestion and so we need to start public awareness willing to use public transport.Keywords: Advertising, Campaign, Trunk, Feeder, Infographic